2014
DOI: 10.11648/j.ajep.20140301.11
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Urban Green Spaces: A Problem Beyond Urbanization in Kumasi City (Ghana)

Abstract: Urbanization remains a single predominant factor that is continuously linked to the destruction of urban green spaces. This has created a knowledge gap of limited attention to other critical factors that deplete urban green spaces in diverse ways. Using Kumasi city (Ghana) which is suffering from rapid deterioration of its green spaces as a study area, this paper sought to fill this gap by exploring other key factors aside urbanization that are responsible for the destruction of urban green spaces. The paper r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 14 publications
2
57
0
2
Order By: Relevance
“…For example, a study by Asare (2013) found many parks in Kumasi to have been converted into commercial centres with the Prince of Wales Park and Kotoko Park (Cricket) being notable examples. Similarly, Adjei Mensah (2014) found substantial portion of the Fante Newtown Park encroached for commercial activities. The Para Gardens was also found to have been taken over by the "Sofoline" interchange.…”
Section: The Current Situation Of Parks and Gardensmentioning
confidence: 95%
See 3 more Smart Citations
“…For example, a study by Asare (2013) found many parks in Kumasi to have been converted into commercial centres with the Prince of Wales Park and Kotoko Park (Cricket) being notable examples. Similarly, Adjei Mensah (2014) found substantial portion of the Fante Newtown Park encroached for commercial activities. The Para Gardens was also found to have been taken over by the "Sofoline" interchange.…”
Section: The Current Situation Of Parks and Gardensmentioning
confidence: 95%
“…There ISSN 2157-6092 2014 www.macrothink.org/jee 97 were a variety of trees along many principal streets of Kumasi which formed canopy and shade for travellers and pedestrians. Typical examples were trees along roads joining "Asarfo" and "Tech" Neighbourhoods, and "Danyame" and "Patasi Neighbourhoods" (Adjei Mensah, 2014). The central business district had several shrubs and lawns which made the commercial hub of the city greener.…”
Section: Landscape Of Kumasi Before 1980mentioning
confidence: 99%
See 2 more Smart Citations
“…Urban greening has received little consideration in Ghanaian cities [74,75], and much less in informal settlements. Studies show that greening and landscaping in urban areas improve social liveliness, enhance aesthetics, and foster environmental behavior settings that support positive spatial and social experiences [70,[76][77][78][79].…”
Section: Implications and Conclusionmentioning
confidence: 99%